Effects of the Color Wheel System on Students With Disabilities in Inclusion Classrooms. Issue 4 (July 2022) - Aspiranti, Kathleen B.
The Color Wheel System (CWS) is a class-wide, rule-based, behavior management strategy that incorporates multiple sets of classroom rules to provide specific behavioral expectations for different classroom activities. This study used the CWS within three inclusion classrooms to evaluate improvements of classroom behavior for students with disabilities. A multiple-baseline design across classrooms evaluated the effects of the CWS on on-task behavior for three students with identified disabilities in each classroom. Momentary time-sampling was used to record on-task behavior, which was operationally defined as eyes on teacher or work or following teacher instructions. Visual analysis of time-series graphs and nonoverlap of all pairs (NAP) measures suggested the CWS caused immediate, large, and sustained increases in on-task behavior for students with disabilities when data are aggregated by classroom. However, individual changes in on-task behavior were variable across students. Implications for using the CWS as part of a class-wide behavioral prevention program and directions for future research are discussed.